Effects of functional genetic polymorphisms in the CYP19A1 gene on prostate cancer risk and survival. Issue 1 (20th May 2014) - Kanda, Sohei; Tsuchiya, Norihiko; Narita, Shintaro; Inoue, Takamitsu; Huang, Mingguo; Chiba, Syuji; Akihama, Susumu; Saito, Mitsuru; Numakura, Kazuyuki; Tsuruta, Hiroshi; Satoh, Shigeru; Saito, Seiichi; et al.
<x xml:space="preserve">Abstract</x> CYP19 catalyzes the conversion of androgens to estrogens and is a critical enzyme affecting the sex hormone milieu. In this study, we investigated the functions of CYP19A1 polymorphisms and their associations with prostate cancer risk and clinical outcome. This case‐control study evaluated the effects of three single nucleotide polymorphisms (SNPs) in CYP19A1 on the risk of prostate cancer in 330 prostate cancer patients and 354 normal controls. The associations between each SNP and sex hormone levels were evaluated in 164 healthy male patients. The functions of the SNPs were determined by reporter gene assays in PC3 and DU145 cell lines. Prostate‐specific antigen nadir was evaluated in 142 patients with metastatic prostate cancer treated with androgen deprivation therapy. Cancer‐specific survival (CSS) was determined in 166 patients with metastatic prostate cancer, to evaluate the influence of the three SNPs. Each variant allele of the three SNPs significantly decreased the risk of prostate cancer. Haplotype analysis showed that the T‐A‐G haplotype (corresponding to rs2470152‐rs10459592‐rs4775936) increased the risk of prostate cancer, while the C‐C‐A haplotype decreased the risk. The estrone/androstenedione ratio was significantly higher in men with the C allele of rs2470152, the C allele of rs10459592, and the A allele of rs4775936 in a gene‐dosage‐dependent manner. Patients with the variant allele at rs4775936 had significantly shorter CSS. These results indicate that CYP19A1 polymorphisms may influence prostate cancer risk and survival by modifying promoter activity, with subsequent effects on the sex hormone milieu.